2023
DOI: 10.1038/s41598-023-30270-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and antiprotozoal activity of silver nanoparticles on viability of Cryptosporidium parvum isolated from pigeons, pigeon fanciers and water

Abstract: Cryptosporidium is a protozoan that causes acute gastroenteritis, abdominal pain, and diarrhea in many vertebrate species, including humans, animals and birds. A number of studies have reported the occurrence of Cryptosporidium in domestic pigeons. Thus, this study aimed to identify Cryptosporidium spp. in samples collected from domestic pigeons, pigeon fanciers, and drinking water, as well as to investigate the antiprotozoal activity of biosynthesized silver nanoparticles (AgNPs) on the viability of isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…It is also the most common cause of diarrhea in children worldwide [ 106 ] because younger children are more susceptible to Cryptosporidium infection [ 107 , 108 ]. Many birds, including chickens, geese, ducks, and pigeons, are known to be biological reservoirs of Cryptosporidium [ 109 ]. The protozoan can be transmitted to humans and animals mainly through the ingestion of contaminated food and drink or through contact with excreta.…”
Section: Antiprotozoal Effect Of Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also the most common cause of diarrhea in children worldwide [ 106 ] because younger children are more susceptible to Cryptosporidium infection [ 107 , 108 ]. Many birds, including chickens, geese, ducks, and pigeons, are known to be biological reservoirs of Cryptosporidium [ 109 ]. The protozoan can be transmitted to humans and animals mainly through the ingestion of contaminated food and drink or through contact with excreta.…”
Section: Antiprotozoal Effect Of Agnpsmentioning
confidence: 99%
“…Additionally, a significant decrease in C. parvum counts was observed after 3, 6, 12, and 24 h of storage for AgNP-treated control C. parvum oocysts at concentrations of 500 µg/mL and 1000 µg/mL, and no oocysts were detected after 48 h of storage for those that were AgNP-treated. The results of the in vivo infectivity test showed that for mice infected with AgNP-treated C. parvum oocysts, C. parvum oocyst counts were significantly lower than that in the control group and showed no infection for AgNPs of 1000 µg/mL for 48 h [ 109 ]. Similar results were obtained by Cameron, et al [ 12 ].…”
Section: Antiprotozoal Effect Of Agnpsmentioning
confidence: 99%
“…Similarly, in Egypt, a study of handlers identified C . parvum in 6% (3/50) of pigeon handlers [19] . Notably, a study in Al-Kut and Al-Zahraa Teaching Hospital in Wasit province found a high prevalence, with 60% (48/80) of patients diagnosed with C .…”
Section: Resultsmentioning
confidence: 99%
“…Sex identification using the CHD gene was first proposed by Griffiths ( Griffiths, 1991 ). At present, this method has achieved early sex identification in chickens ( Ayers et al, 2015 ), ducks ( Li et al, 2015 ), pigeons ( Abou Elez et al, 2023 ), partridges ( Jia et al, 2023 ), ostriches ( Huang C and Huang M, 2008 ), and other species. There are two homologous copies of the CHD gene, of which CHD1-W is linked to the W chromosome and CHD1-Z is linked to the Z chromosome ( Lai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%